2003
DOI: 10.1046/j.1365-2486.2003.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐surface carbon dioxide efflux and microbial biomass in relation to tree density 13 years after a stand replacing fire in a lodgepole pine ecosystem

Abstract: The effects of fire on soil‐surface carbon dioxide (CO2) efflux, FS, and microbial biomass carbon, Cmic, were studied in a wildland setting by examining 13‐year‐old postfire stands of lodgepole pine differing in tree density (< 500 to > 500 000 trees ha−1) in Yellowstone National Park (YNP). In addition, young stands were compared to mature lodgepole pine stands (∼110‐year‐old) in order to estimate ecosystem recovery 13 years after a stand replacing fire. Growing season FS increased with tree density in young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 71 publications
5
67
1
1
Order By: Relevance
“…Microbial biomass changed among the three sampling dates, with the highest biomass in April, the period of peak photosynthesis (Waring and Franklin 1979), and the lowest values in November, when the soils were saturated and fairly cold. Seasonal changes in microbial biomass have been reported in other studies in forest ecosystems, although the season of high biomass varied with respect to climate and tree physiology (Myers et al 2001;Bohlen et al 2002;Litton et al 2003).…”
Section: Seasonal Dynamics At Andmentioning
confidence: 60%
“…Microbial biomass changed among the three sampling dates, with the highest biomass in April, the period of peak photosynthesis (Waring and Franklin 1979), and the lowest values in November, when the soils were saturated and fairly cold. Seasonal changes in microbial biomass have been reported in other studies in forest ecosystems, although the season of high biomass varied with respect to climate and tree physiology (Myers et al 2001;Bohlen et al 2002;Litton et al 2003).…”
Section: Seasonal Dynamics At Andmentioning
confidence: 60%
“…TBCF was also tightly linked to ANPP total across large gradients in tree density and stand age in Pinus contorta forests (Litton et al, 2004). Soil-surface CO 2 efflux (F soil ) is the largest flux within the mass balance equation for estimating TBCF (Giardina & Ryan, 2002;Litton et al, 2003a), and there is an increasing appreciation of a tight link between carbon fixed in the forest canopy and the flux of carbon from soils as CO 2 (Hö gberg et al, 2001;Irvine et al, 2005). However, other studies have shown a lack of correlation between F soil or TBCF and ANPP across diverse forested landscapes (Campbell et al, 2004).…”
Section: Fluxmentioning
confidence: 99%
“…8c). One exception was lodgepole pine stands in Wyoming, where partitioning to ANPP foliage decreased in older stands (Litton et al, 2003a(Litton et al, , 2004. Another exception were the Eucalyptus saligna stands in Hawaii, where partitioning to ANPP wood decreased and to TBCF increased with age .…”
Section: Partitioning To Respirationmentioning
confidence: 99%
“…Soil respiration can be characterized by biological processes, including the combination of autotrophic respiration by live roots and their associated mycorrhizae, and heterotrophic respiration by microbes that oxidize plant detritus, root exudates and humified organic matter [13][14]. The exchange of CH 4 between the soil and atmosphere is regulated by two disparate groups of microorganisms, calledmethanotrophic bacteriaand methanogenic bacteria [15].The most of CH 4 emission from soil occurs largely due to the action of methanogenic bacteria in anaerobic conditions, and the most of the CH 4 consumption by methanotrophic bacteria in aerobic conditions [15].…”
Section: Introductionmentioning
confidence: 99%